Shared Leadership on a Career and Technical Education Campus - Samantha Ward; Casey Graham-Brown (School Leadership Review, 2018)
Many students enter career and technical education (CTE) programs to pursue the attainment of job-specific skills. K-12 career and technical education program educators help prepare students for careers after high school by offering students a way to establish and improve upon industry-based skills (Treschan & Mehrotra, 2014). Through CTE programs, educators train students to become global competitors in the workforce by introducing them to career practices that are prominent within their fields (Conley, 2013; Gordon, 2014; Stone & Lewis, 2012).